Intra-household joint decision making on child feeding and associated social determinants in rural districts of South Ethiopia: a multi-site concurrent mixed method study - Kassahun Fikadu; Abinet Takele; Biruk Tesfaye; Zeleke Hailemariam Abebo (Frontiers in Public Health)
BackgroundImproving joint intra-household decision-making by spouses is a promising solution to improve child-feeding practices. Therefore, this study aimed to assess the status and barriers of intra-household joint decision making on child feeding in rural districts of South Ethiopia from the perspectives of primary caregivers and key individuals.MethodsA mixed-method study was conducted from July 15 to September 15, 2023 in three randomly selected rural districts: Arba Minch Zuria, Mierab Abaya, and Chencha, in Southern Ethiopia. We employed a cross-sectional study design to collect quantitative data. A computer generated random number technique was used to include 25% of the total kebeles from each district. A total of 20 kebeles; 8 from 32 kebeles of chencha, 6 from 24 kebeles of Mierab Abaya, and 6 from 24 kebeles of Arba Minch Zuria were included. A total of 1,479 women with their children aged 6–23 months were recruited from family folder of the health extension program using a simple random sampling technique. A descriptive qualitative study design was used to collect data from 51 focus group discussants and 12 key informants. Trained health professionals collected the data using a structured and pre-tested interviewer administered questionnaire and semi-structured interviewer guide for quantitative and qualitative data, respectively. Univariate analysis was used to determine the frequency and percentages while Binary logistic regression analysis was employed to identify the associated factors. The odds ratio with a 95%CI was computed to assess strength of the association. The principles of saturation were adhered during the qualitative data collection. Thematic analysis was used to analyze the data in themes and subthemes, using ATLAS.ti version 23.ResultsOverall, more than two-thirds (69.2%) of the intra-household decision-making regarding child feeding were found to be jointly decided by the spouses. Women with formal education (AOR = 1.84, 95% CI: 1.37–2.46), husband involvement in child feeding (AOR = 2.23, 95%CI: 1.70–2.92), having fewer than or equal to three children (AOR = 1.51, 95%CI: 1.11–2.04), women aged 25-34 years (AOR = 1.57, 95%CI: 1.19–2.07) and 35-49 years (AOR = 2.14, 95%CI: 1.38–3.33) were significantly associated with joint decision-making regarding child feeding practices. Moreover, large family sizes, large age gaps between husbands and wives, and gender inequalities were identified as barriers to women’s engagement in intra-household decision making based on qualitative analysis.ConclusionIn the rural districts of southern Ethiopia, joint intra-household decision making regarding child feeding was found to be satisfactory. Maternal education, husband’s involvement in child feeding, mother’s age, and number of children were independent variables that significantly influenced women’s engagement in joint intra-household decision making on child feeding. Interventions targeted at improving women’s engagement in decision-making should consider the following sociocultural barriers: extreme age differences between couples, large family sizes, and detrimental gender-oriented norms.